Landfarmed oil sludge could be used as a fertilizer for jack-beans (canavalia ensiformis) implications on phytoremediation (2009)
The petroleum exploitation in the oilfields, especially petroleum drilling, generates an oily sludge mixed with hydrocarbons and mineral solids. This is an important waste that could generate an environmental problem. In general, these oil sludge's are treated chemically or stored in deposits. In either case, it is sometimes treated by bioremediation and phytoremediation. Some waste sludge's have been used as a fertilizer or soil additions. The objective of this study was to assess the influence of land farmed oil sludge as a fertilizer of the legume C. ensiformis in a phytoremediation assay of the TPHs remnants in this oil sludge. Also different parameters were evaluated in order to identify morphological differences of the legumes between the soil added with the oil sludge and control soil amended with humus. Since there were no differences in the plant height and leaf area between treatments during the study, it can be considered that the oil sludge does not affect the plants as a soil addition. There was a decrement of TPH levels in the soil and an accumulation of TPHs in the roots. The TPHs were not found in the aerial parts of the plants, however there were some PAHs. Endophytes of the Enterobacteriaceae family were found in the plants of the oil sludge treatment, but it could not be proved that these endophytes are involved in the remediation of these organic compounds. In future studies, it could be possible to identify the bioremediation capacity in the isolated endophytes. It is important to continue with the phytoremediation with successive crop rotation.